2017
DOI: 10.7127/rbai.v11n300577
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade E Eficiência De Uso Da Água Em Milho Cultivado Com Diferentes Estratégias De Manejo Hídrico

Abstract: 1 Professor doutor, Faculdade de Ciências Agrárias, UFGD, Dourados -MS, almeidaacs@yahoo.com.br 2 Eng. Agricola, Faculdade de Ciências Agrárias, UFGD, Dourados -MS 3 Doutorando em Engenharia de Sistemas Agrícolas, ESALQ-USP, Piracicaba, SP RESUMOO objetivo desta pesquisa foi avaliar diferentes estratégias de manejo da irrigação sobre a produtividade e eficiência de uso da água na cultura do milho. Um experimento foi conduzido no delineamento experimental inteiramente casualizado (em faixas), com quatro tratame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
7
1
Order By: Relevance
“…However, in the 2013 year, the hybrid AS 1555 showed the highest yield (9338 kg ha -1 ) when sown in February (156 bags ha -1 ), corresponding to an increase of 44% from rainfed conditions (Figure 1). Such values are higher than those obtained by Almeida et al (2017) in a study in the same region (Dourados/MS), evaluating water management strategies on corn yield in the 2013/2014 crop year. These authors obtained an average yield of 8955 kg ha -1 (149 bags ha -1 ) when irrigated.…”
Section: Resultscontrasting
confidence: 64%
See 3 more Smart Citations
“…However, in the 2013 year, the hybrid AS 1555 showed the highest yield (9338 kg ha -1 ) when sown in February (156 bags ha -1 ), corresponding to an increase of 44% from rainfed conditions (Figure 1). Such values are higher than those obtained by Almeida et al (2017) in a study in the same region (Dourados/MS), evaluating water management strategies on corn yield in the 2013/2014 crop year. These authors obtained an average yield of 8955 kg ha -1 (149 bags ha -1 ) when irrigated.…”
Section: Resultscontrasting
confidence: 64%
“…The irrigated plants had a height of 183.88 cm, which corresponds to an increase of 13.33% in relation to rainfed plants. Almeida et al (2017) studied crop yield and water-use efficiency in corn grown under different water management strategies and observed that plant height, dry matter and ear mass were also higher for irrigated crops.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature has shown several problems related to WD which result in stress, thus, jeopardizing grass species such as corn (Zea mays L.; Almeida et al, 2017), barley (Hordeum vulgare L.; Sanches et al, 2015), wheat (Triticum aestivum L.; Raheem et al, 2017), rice (Oryza sativa L.; Wei et al, 2017) and Urochloa sp. (Odokonyero et al, 2017).…”
Section: Physiological Mechanisms In Response To Water Deficitmentioning
confidence: 99%